2013
DOI: 10.1016/j.physletb.2013.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic properties of doubly charmed baryons in Lattice QCD

Abstract: We compute the electromagnetic properties of Ξcc baryons in (2+1)-flavor Lattice QCD. By measuring the electric charge and magnetic form factors of Ξcc baryons, we extract the magnetic moments, charge and magnetic radii as well as the ΞccΞccρ coupling constant, which provide important information to understand the size, shape and couplings of the doubly charmed baryons. We find that the two heavy charm quarks drive the charge radii and the magnetic moment of Ξcc to smaller values as compared to those of, e.g.,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 45 publications
3
47
0
Order By: Relevance
“…We have argued in ref. [5] that such behavior may be related to the modification of the confinement force in the hadrons.…”
Section: Jhep05(2014)125mentioning
confidence: 96%
See 2 more Smart Citations
“…We have argued in ref. [5] that such behavior may be related to the modification of the confinement force in the hadrons.…”
Section: Jhep05(2014)125mentioning
confidence: 96%
“…[4,5] for the details of our lattice setup. We use four sets of configurations with different light quark hopping parameters κ u,d sea = 0.13700, 0.13727, 0.13754, JHEP05(2014)125 Figure 1.…”
Section: Lattice Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that the doubly charged Σ ++ c has the largest electric charge radius amongst the baryons that we considered. The electric charge radii of Ω + cc and Ξ + cc [2] are about the same size which suggests that electric charge radius is insensitive to replacing the light d-quark by an s-quark. We observe that the electric charge radii is much smaller compared to that of the proton (the PDG value is r 2 E,p =0.770 fm 2 [13]).…”
Section: Resultsmentioning
confidence: 93%
“…The framework of lattice QCD enables us to determine such form factors starting from quark and gluon degrees of freedom. In our previous works we have found that the existence of a charm quark drives the charge radii and magnetic moments of the hadrons to smaller values [1,2]. Yet it is interesting to see how the charge radii are affected as the light quark gets heavier as in the case of replacing the u/d quark by an s quark.…”
Section: Introductionmentioning
confidence: 99%